Immunity-Boosting Metal Complexes - KUMARI, K KRISHNA; SREEDEVI, GADDAM; RAJESWARI, NEELAPUDI (The journal of contemporary issues in business and government, 2019)
Emerging infectious illnesses and a growing number of multidrug-resistant microbiological pathogens combine to make the treatment of infectious diseases a significant and difficult challenge. Still, there are a lot of availability of antibiotics and chemotherapeutics for medical use and the rise of to both older and more recently developed antibiotics has increased dramatically during the last several decades. Antimicrobial drug development is urgently needed in the medical field. For the most part, people believe that they require the isolation of hitherto unknown chemicals having antibacterial properties, which may method of action that is different from those of established groups of antibacterial antibiotics, drugs, etc., against which many common infections have developed resistance in clinical settings.